Apakah phubbing mengganggu pertemanan? Hubungan phubbing dengan kepuasan pertemanan pada orang beranjak dewasa - Sri Fatmawati Mashoedi; Putri Sulistiani Adi Pekerti (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
This study aims to determine the relationship between phubbing and friendship satisfaction of emerging adults. The respondents of this study were 166 students aged 18-25 years who studied at universities and lived in Jakarta, Depok, Bogor, Tangerang, and Bekasi. They were selected using accidental sampling techniques by meeting with them on their respective campuses. Correlation index calculation showed there was no significant relationship between phubbing and friendship satisfaction (r = .13, p > 0.05). Based on the regression analysis, it was found that phubbing behavior could not predict friendship satisfaction (b = 0.08, t = 1.7, p> 0.05) and it can be concluded that phubbing behavior is not at the level to the point of disturbing the quality of their friendships. Limitations of this study and directions for further research are further discussed.